Segmentectomy preserves better immune-nutritional status than lobectomy in patients with early-stage lung cancer. (24th January 2023) - Kamigaichi, Atsushi; Mimae, Takahiro; Amioka, Jun; Aoki, Gaku; Yoshimura, Kenichi; Kawamoto, Nobutaka; Tsubokawa, Norifumi; Miyata, Yoshihiro; Okada, Morihito
Abstract: OBJECTIVES: This study aimed to compare the postoperative immune-nutritional status of patients undergoing segmentectomy and lobectomy for early-stage non-small-cell lung cancer. METHODS: Patients with clinical stage 0–IA non-small-cell lung cancer who underwent lobectomy or segmentectomy were retrospectively analysed. Postoperative immune-nutritional indices (prognostic nutritional index, serum albumin levels and total lymphocyte count) at 1 month, 6 months, 1 year, 2 years and 3 years after surgery were compared using mixed effects linear models and mixed effects logistic regression models. RESULTS: There were 164 and 210 patients in the lobectomy and segmentectomy groups, respectively. Postoperative prognostic nutritional index and albumin levels were significantly higher in the segmentectomy group than those in the lobectomy group ( P  <   0.001 and P  <   0.001, respectively), despite the nonsignificant difference in the total lymphocyte count ( P  =   0.563). In 126 propensity score-matched pairs adjusted for confounding variables affecting postoperative nutritional status, postoperative prognostic nutritional index and albumin levels were significantly higher in the segmentectomy group than in the lobectomy group ( P  =   0.009 and P  =   0.007, respectively). At each time point after surgery, these indices were higher in the segmentectomy group than in the lobectomy group at 1 month, 2 years and 3 years postoperatively. There were significantly more patients with lower immune-nutritional indices (prognostic nutritional index <45, albumin <4.0 g/dl) in the lobectomy group than in the segmentectomy group at 3 years postoperatively ( P  =   0.026 and P  =   0.029, respectively), despite nonsignificant statistical differences throughout the study period ( P  =   0.219 and P  =   0.113, respectively). CONCLUSIONS: Patients who underwent segmentectomy showed better postoperative immune-nutritional status than those who underwent lobectomy. Abstract : Recent developments in high-resolution, low-dose computed tomography (CT) have improved the detection of early-stage lung cancer.